Hubungan HUBUNGAN ANTARA KONFORMITAS DENGAN PERILAKU PROSOSIAL PADA PEDAGANG UMKM DI KOTA SALATIGA - Nico, Theodoros (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study aims to examine the relationship between conformity and prosocial behavior among Micro, Small, and Medium Enterprise traders in Salatiga City. A quantitative correlational method was employed, with the population consisting of MSME traders in Salatiga and a purposive sampling technique yielding 104 participants. The instruments used were the Prosocial Tendencies Measure (PTM) to assess prosocial behavior and The Conformity Scale to measure conformity. Data were analyzed using Spearman’s correlation due to non-normal distribution and non-linear relationships between variables. The results revealed a significant positive relationship between conformity and prosocial behavior (r = 0.242; p = 0.013), indicating that higher conformity is associated with greater tendencies to display prosocial actions. These findings have practical implications for Micro, Small, and Medium Enterprise development programs, emphasizing the need to strengthen group norms while fostering psychological and social factors that encourage sustainable prosocial practices.